Towards a Modernized Geodetic Datum for Nepal Following the April 25, 2015 Mw 7.8 Gorkha Earthquake - Pearson, Chirstopher; Manandhar, Niraj (Journal on Geoinformatics, Nepal, 2016)
Along with the damage to buildings and infrastructure, the April 25, 2015 Mw 7.8 Gorkha earthquake caused quite significant deformation over a large area in central Nepal with displacements of over 2 m recorded in the vicinity of Kathmandu. In this paper we consider options for a modernized geodetic datum for Nepal that will have the capacity to correct for the earthquake displacements and ongoing tectonic deformation associated with Nepal’s location on the India/Eurasian plate boundary. In the scenario we present here, the datum would be based on ITRF2014 with a reference epoch set some time after the end of the current sequence of earthquakes. We have developed a preliminary velocity field by collating GPS derived crustal velocities from four previous studies for Nepal and adjacent parts of China and India and aligning them to the ITRF. We developed preliminary patches for the coseismic part of the deformation using published dislocation models. By combing the velocity and coseismic models we have developed an NDM that can correct coordinate for both the effect of the earthquakes and continuous deformation associated with Indian / Eurasian plate boundary. High order control would be a CORS network based around the existing Nepal GPS Array. Coordinates for existing lower order control would be determined by readjusting existing survey measurements and these would be combined with a series of new control stations spread throughout Nepal.